Pengaruh Perasan Sargassum crassifolium dengan Konsentrasi yang Berbeda terhadap Pertumbuhan Tanaman Kedelai (Glycine max (L) Merill) - Kusumaningrum, Indri; Hastuti, Rini Budi; Haryanti, Sri (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2007)
Soybean is one important vegetable in Indonesia, soybean consist of 35 gram of protein for every 100 gram. Even more upon consist of the superior variety. Contains soybean protein could reach 40 – 43% to interest the growth of soybean plants. We can complete various methods, one of them is the use of see weed, because it consist of high phytohormone. Sargassum crassifolium is one see weed of phaephy Cese Class that is potential to accelerate growth of plants from other species. Compounds consisted inside are auxin, giberelin, cytolaninand other mineral etc. The purpose of the research is to acknowledge the effect of Sargassum crassifolium extract with different concentration toward the growth of soybean plants and acknowledge the extract concentration that effect to the growth of soybean plants. This research was executed in October – November 2001 in Green House and the Laboratory of Structure and Plant function Biology F.MIPA UNDIP. The research lay out used was the extract of Sargassum crassifolium with concentration of 25%, 50%, 75%, 100% and without extract ( 0% ). Each treatment was repeated for 5 time. The gained data was analyzed with variety investigation analyzed were real difference level of 5%. The research result shows that the extract of Sargassum crassifolium effects to plant heigh, but it does not effect to number of leaf, wet weight and dry weight soybean plant. The plant height in creases upon the extrct concentration of Sargassum crassifolium of 50%.